Separation and Characterization of New Transition Metal Complexes of some Chromone Derivatives - S. Youssef, Nabil (Asian Journal of Chemistry, 2010)
Some transition metal complexes of 5-[7-hydroxy-5-methoxy-2-methyl chromonelidene] barbituric acid (H2L1) and 5-[5,7-dihydroxy-2-methyl chromonelidene] thiobarbituric acid (H3L2) have been separated and characterized by elemental analyses, IR and electronic spectra and thermogravimetric analyses. Square-planar structures are suggested for the Cu(II) and Pd(II) complexes, whereas octahedral structures are proposed for the Cr(III), Ni(II), Co(II), Pt(IV) and Rh(III) complexes.